Film Review - Beginning (2020) - Tsitsi-Sopo Kevkhishvili (Slovo, 2021)
This film review analyses Beginning, a debut feature by a young Georgian director Dea Kulumbegashvili. It attempts to explore and unpack the female character, who, being persecuted by religious fanaticism and manhood, suffers an existential crisis. The review also turns to the cinematography. dramaturgy, and aesthetics of the film.
Keywords: film; Georgian film; gender; Dea Kulumbegashvili